Total Phenolic and Coumarin Content, Antioxidant Activity of Leaves, Fruits, and Stem Barks of Grey Mangrove (Avicennia marina) - Alik Kandhita Febriani; Ismiyarto Ismiyarto; Khairul Anam (Jurnal Kimia Sains dan Aplikasi, 2020)
Avicennia marina is one of the mangrove species used for traditional medicines. The leaves, fruits, and stem barks of A. marina are used for treating skin diseases. The stem barks are used for rheumatism, smallpox, and ulcers. The extract of A. marina was also reported to have antioxidant activity and indicates the presence of alkaloid, saponin, flavonoid, tannin, sterol/triterpenoid, and coumarin. However, the comparison of the antioxidant activity of leaves, fruits, and stem barks is not evaluated yet. The purpose of this study is to compare the antioxidant activity, total phenolic and coumarin content of leaves, fruits, and stem barks of A. marina. The antioxidant activity was determined using DPPH radical scavenging assay and was evaluated by spectrophotometric method at 515 nm. Quercetin was used for comparison. The fruits had the highest antioxidant activity with an IC50 value of 85.246 ppm, followed by stem barks and leaves with IC50 of 205.281 ppm and 307.037 ppm, respectively. Although the antioxidant activity of A. marina fruits was far from quercetin (IC50 of 3.789 ppm), it still categorized as a strong antioxidant. The strong antioxidant activity of fruits was followed by higher total phenolic and coumarin content than the stem barks and leaves part. Total phenolic and coumarin content of fruits were 49.119 mg GAE/ g and 8.894 x 10-3 mg CE/g, respectively. The leaves part had total coumarin content of 8.418 x 10-3 mg CE/g, but it had low IC50. It may be caused by the other secondary metabolite compounds that could reduce the antioxidant activity of coumarin.